Systemic administration of propranolol reduces bone resorption and inflammation in apical periodontitis of chronically stressed rats - Khoury, Rayana Duarte [UNESP]; Minhoto, Giovanna Bignoto [UNESP]; de Barros, Patricia Pimentel; Junqueira, Juliana Campos [UNESP]; Gagliardi, Carolina Fedel [UNESP]; do Prado, Renata Falchete [UNESP]; Valera, Marcia Carneiro [UNESP] (Wiley, 2024)
Aim: To evaluate the effect of systemic administration of propranolol on the severity of apical periodontitis (AP) in chronically stressed rats. Methodology: Twenty-four 70-day-old male Wistar rats (Rattus norvegicus, albinus) were distributed into three groups (n = 8): rats with AP without stressful conditions (AP-Control), rats with AP and submitted to a chronic unpredictable stress (CUS) protocol (AP + S) and rats with AP and submitted to a CUS protocol treated with propranolol (AP + S + PRO). Stress procedures were applied daily until the end of the experiment. After 3 weeks of CUS, AP was induced in all groups by exposing the pulpal tissue of mandibular and maxillary first molars to the oral environment. Propranolol treatment was administered orally once a day for the entire period of the experiment. Rats were sacrificed at 42 days, and the blood was collected for stress biomarkers serum dosage by multiplex assay. Mandibles were removed and submitted to microtomography and histopathological analyses. Periapical tissue surrounding the upper first molar was homogenized and subjected to RT-PCR analysis to evaluate the mRNA expression of RANKL, TRAP and OPG. Parametric data were assessed using one-way ANOVA followed by Tukey's test while the nonparametric data were analysed by the Kruskal–Wallis followed by Dunn's test. Significance level was set at 5% (p <.05) for all assessed parameters. Results: Micro-CT revealed statistically significant differences in bone resorption which was greater in the AP + S group (p <.05), but no differences were observed between the Control and AP + S + PRO groups (p >.05). The AP + S + PRO group had a lower intensity and extent of inflammatory infiltrate compared to the AP + S group with smaller areas of bone loss (p < 0.05). The gene expression of RANKL and TRAP was significantly higher in the stressed group AP + S compared to the control group (p <.05), and a significantly higher OPG expression was observed in AP + S + PRO compared to the AP + S group (p <.05). Conclusions: Oral administration of propranolol had a significant effect on the AP severity in stressed rats, suggesting an anti-inflammatory effect and a protective role on bone resorption of AP in stressed animals. Further research is necessary to fully comprehend the underlying mechanisms.
Keywords: animal model; apical periodontitis; chronic stress; endodontics; propranolol